Procurement PoliciesandImplementation Of Effective Procurement Practices In Tertiary Public Training Institutions In Kenya - Njeru, Silas E.; Ngugi, Patrick; Arasa, Robert; Kahiri, James. (My University, 2014)
Procurement policies are rules and regulations for governing procurement procedures in an organization. A properly designed and implemented procurement policy plays a pivotal role in providing a guiding framework for the implementation of efficient procurement practices. In Kenya, over 70% of tertiary public training institutions procurement practices are normally not in full compliance with Public Procurement and Disposal Act, 2005 and Public Procurement and Disposal Regulations, 2006. This study set out to establish the influence of procurement policies on implementation of effective procurement practices in tertiary public training institutions in Kenya. The study employed a descriptive research designs, targeting procurement staff across the 40 tertiary public training institutions in Kenya. A stratified random sampling technique was employed to select a sample size of 160 respondents. The main data collection instrumentwas a questionnaire containing open ended and closed ended questions utilizing both a nominal and a Likert-type scale format. The study findings shows that procurement policies elements that influence implementation of effective procurement practices in tertiary public training institutions in Kenya included; low level of procurement regulations compliance, application of poor procurement policies, lack of top management support, use of poor procurement procedures, poor relationship between management and stakeholders, poor method of managing organization resources and lack of effective policy making process. The study recommends that the management of the tertiary public training institutions should improve on the level of compliance with procurement regulations, design and apply better procurement policies, support and empower staff to execute procurement functions in accordance with the procurement regulations and procurement policies, use effective procurement procedures, improve on relationship between management and stakeholders and employ better methods of managing organization resources
Keywords: Procurement policies; Effective Procurement Practices